Gender differences in children's mathematics achievement: Perspectives from the Longitudinal Study of Australian Children - Carmichael, Colin (My University, 2013)
With reports of declining enrolments in mathematics related degrees and low female participation rates in these degrees, the issue of gender differences in mathematics remains relevant. Results of recent studies suggest gender differences in mathematics are nuanced and that small differences in the early years can manifest as larger differences in later years. This study explores differences in teachers’ ratings of children’s achievement across a number of mathematical content domains. It is based on observations from the K-cohort of the Longitudinal Study of Australian Children in 2006, when the children were aged between six and seven, and in 2008, when they were aged between eight and nine. Gender differences in achievement are analysed using the Mantel-Haenszel procedure associated with the implementation of the Rasch model. Results indicate that teachers rate girls higher on tasks related to data, whereas they rate boys higher on tasks related to place-value and computation. Implications of these findings are discussed.
Keywords: Education and Training -- Literacy and numeracy; Gender -- Gender differences; Gender; Learning, education and training; Education and Training; Gender; Gender differences; Literacy and numeracy; Learning, education and training; Gender